2016
DOI: 10.1155/2016/4612167
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells as a Prospective Therapy for the Diabetic Foot

Abstract: The diabetic foot is a serious complication of diabetes. Mesenchymal stem cells are an abundant source of stem cells which occupy a special position in cell therapies, and recent studies have suggested that mesenchymal stem cells can play essential roles in treatments for the diabetic foot. Here, we discuss the advances that have been made in mesenchymal stem cell treatments for this condition. The roles and functional mechanisms of mesenchymal stem cells in the diabetic foot are also summarized, and insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 166 publications
0
22
0
Order By: Relevance
“…Compared to the hydrogel group, the addition of GMSC-derived exosomes significantly promoted the nerve density, which suggests that the GMSC-derived exosomes could facilitate neuronal ingrowth to the wound bed. Previous studies have found that MSCs could promote nerve growth, restoration of neuropathic morphology and nerve function in diabetic rats, and the main mechanism is the secretion of nerve growth factor (NGF) by the MSCs, which can in turn promote the regeneration of nerve fibers (Sun et al, 2012 ; Xia et al, 2015 ; Wu et al, 2016 ). However, to our knowledge, there are no studies focused on the effects of MSC-derived exosomes on neuronal growth in diabetic rat skin defect model at present, and our results provide new evidence that the use of MSC-derived exosomes may be a promising method to promote the healing of chronic wounds in DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the hydrogel group, the addition of GMSC-derived exosomes significantly promoted the nerve density, which suggests that the GMSC-derived exosomes could facilitate neuronal ingrowth to the wound bed. Previous studies have found that MSCs could promote nerve growth, restoration of neuropathic morphology and nerve function in diabetic rats, and the main mechanism is the secretion of nerve growth factor (NGF) by the MSCs, which can in turn promote the regeneration of nerve fibers (Sun et al, 2012 ; Xia et al, 2015 ; Wu et al, 2016 ). However, to our knowledge, there are no studies focused on the effects of MSC-derived exosomes on neuronal growth in diabetic rat skin defect model at present, and our results provide new evidence that the use of MSC-derived exosomes may be a promising method to promote the healing of chronic wounds in DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Having such a perivascular location, MSCs have been shown to promote blood and lymphatic vessel formation and stability as support niche cells for vascular regeneration, by recruiting circulating vascular progenitor cells or by releasing pro-angiogenic factors. 10,[23][24][25] The effects of MSCs on vascular regeneration have been found to be beneficial for wound healing, [26][27][28] attenuation of limb ischemia, 29 or reperfusion of infarcted heart. 30 Apart from their effects on vascular cells, MSCs can modulate various immune cells including monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the novel cell therapy was assigned to this patient to eradicate its potential recurrence. Since 2005, our team has been dedicated to the therapeutic use of different stem cells for diabetic wound repair and limb salvage [ 6 , 7 , 12 14 ]. Both BMMSCs and bone marrow-derived mononuclear cells have been used for diabetics with critical limb ischemia and foot ulcer, the former producing better clinical outcomes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%